Rancang Bangun dan Uji Performansi Alat Pembuka Katup Menggunakan Mekanisme Tuas - Leo Dedy Anjiu; Suhendra Suhendra; Irma Fahrizal (Jurnal Engine: Energi, Manufaktur, dan Material, 2021)
The increasing number of vehicles every year provides opportunities to vehicles service. Vehicle components that often serviced or overhaul is the valve mechanism. How to remove the valve from the cylinder head generally use a manual valve remove tool. The time required to remove the valve using the tools need a long time. Effort to overcome these problems is to modify the existing valve remove mechanism. The purpose of this research is to design and test the performance of valve remove using lever mechanism. Performance test was conducted to determine the press force value to remove the valve, the percentage increase performance and time to remove the valve. The main components of the valve remove tool using the lever mechanism is frame, table, pole support, locking, hand grips, hydraulic, lever pusher and shaft sled. Testing using the valve mechanism is contained in the cylinder head Toyota Kijang 4K. The valve remove tool design has a simple form, easy to make, cheap, but has very good performance. The smallest of the press force to remove the valve is 129 N obtained at a distance of lock and poles support as far as 22 cm. The valve remove tool using the lever mechanism was design can remove the valve from the cylinder head in time 26,17 seconds/valve or 418,67 seconds to remove 16 valves on the cylinder head. This tool is able to improve the performance of manual valve remove tool screw type by 76,28%, and can improve the performance valve remove tool the pneumatic system by 65,79%.